Fullerenes Influence the Toxicity of Organic Micro-Contaminants to River Biofilms - Freixa, Anna; Acuña, Vicenç; Gutierrez, Marina; Sanchís, Josep; Santos, Lúcia H. M. L. M.; Rodriguez-Mozaz, Sara; Farré, Marinella; Barceló, Damià; Sabater, Sergi (Frontiers in Microbiology, 2018)
Organic micro-contaminants (OMC) enter in freshwaters and interact with other contaminants such as carbon nanoparticles, becoming a problem of unknown consequences for river ecosystems. Carbon nanoparticles (as fullerenes C60) are good adsorbents of organic contaminants and their interaction can potentially affect their toxicity to river biofilms. We tested the C60 interactions with selected OMCs and their effects on river biofilms in different short-term experiments. In these, river biofilms were exposed to C60 and three OMC (triclosan, diuron or venlafaxine) and their respective mixtures with fullerenes (C60 + each OMC). The effects were evaluated on structural, molecular and functional descriptors of river biofilms. Our results showed that C60 did not cause toxic effects in river biofilms whereas diuron and triclosan significantly affected the heterotrophic and phototrophic components of biofilms and venlafaxine affected only the phototrophic component. The joint exposure of C60 with venlafaxine was not producing differences with respect to the former response of the toxicant, but the overall response was antagonistic (i.e., decreased toxicity) with diuron, and synergistic (i.e., increased toxicity) with triclosan. We suggest that differences in the toxic responses could be related to the respective molecular structure of each OMC, to the concentration proportion between OMC and C60, and to the possible competition between C60-pollutants on blocking the receptors of the biological cell membranes. We conclude that the presence of C60 at low concentrations modified the toxicity of OMC to river biofilms. These interactions should therefore be considered when predicting toxicity of OMC in river ecosystems.